Learning Evaluation Using Block Programming on Object-Oriented Programming Materials to Improve Cognitive Skills - Kirana Syafa Huda; Latifahny Aridia Alfitri; Raseeda Hamzah; Lala Septem Riza (CV. Media Inti Teknologi, 2025)
Background: Vocational students in Indonesia face low cognitive performance due to curricula that emphasize memorization and shallow understanding. In programming subjects such as Object-Oriented Programming (OOP), students often manage to write syntactically correct code but struggle with conceptual mastery. This limits their ability to develop higher-order thinking skills such as analysis, evaluation, and creation.Aims: This study aims to evaluate the use of block programming in OOP materials and its impact on improving students’ cognitive abilities in class X PPLG 3 at SMKN 4 Bandung.Methods: A quantitative approach was applied using a one-group pretest–posttest experimental design. Research instruments included expert validation sheets, cognitive evaluation tests, and student response questionnaires. Data were collected from 34 students to measure learning improvementResults: The findings revealed a significant increase in student performance, with average scores rising from 27.03 (pretest) to 85.47 (posttest). The N-Gain score reached 0.80 (80.29%), categorized as “high.” Student responses toward block programming media reached 93.61%, showing strong engagement. The integration of block programming with Problem-Based Learning (PBL) provided a contextualized and intuitive approach, transforming abstract OOP concepts into more tangible visual representations.Conclusion: Block programming is effective as a learning evaluation medium in OOP. It supports cognitive development, enhances student engagement, and simplifies complex concepts. This study recommends the broader use of block programming in evaluating OOP learning to create interactive and measurable experiences.